First confirmation and characterization of target and non-target site resistance to glyphosate in Palmer amaranth (Amaranthus palmeri) from Mexico - Dominguez-Valenzuela, Jose Alfredo; Gherekhloo, Javid; Fernández-Moreno, Pablo Tomás; Cruz-Hipolito, Hugo Enrique; Cruz, Ricardo Alcántara-de la; Sánchez-González, Eduardo; Prado, Rafael De (Plant Physiology and Biochemistry, 2017)
Following the introduction of glyphosate-resistant (GR)-cotton crops in Mexico, farmers have relied upon glyphosate as being the only herbicide for in-season weed control. Continuous use of glyphosate within the same year and over multiple successive years has resulted in the selection of glyphosate resistance in Palmer amaranth (Amarantus palmeri). Dose-response assays confirmed resistance in seven different accessions. The resistance ratio based on GR50 values (50% growth reduction) varied between 12 and 83. At 1000 μM glyphosate, shikimic acid accumulation in the S-accession was 30- to 2-fold higher at compared to R-accessions. At 96 h after treatment, 35–44% and 61% of applied 14C-glyphosate was taken up by leaves of plants from R- and S-accessions, respectively. At this time, a significantly higher proportion of the glyphosate absorbed remained in the treated leaf of R-plants (55–69%) compared to S-plants (36%). Glyphosate metabolism was low and did not differ between resistant and susceptible plants. Glyphosate was differentially metabolized to AMPA and glyoxylate in plants of R- and S-accessions, although it was low in both accessions (<10%). There were differences in 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS) enzyme activity by 50% (I50) between R- and S-accessions. However, no significant differences were found in the basal EPSPS activity (μmol inorganic phosphate μg−1 total soluble protein min−1) between R- and S-accessions. A point mutation Pro-106-Ser was evidenced in three accessions. The results confirmed the resistance of Palmer amaranth accessions to glyphosate collected from GR-cotton crops from Mexico. This is the first study demonstrating glyphosate-resistance in Palmer amaranth from Mexico.
Keywords: Glyphosate; Herbicide resistance; Metabolism; Palmer amaranth; Translocation; Pro-106